Concepções de leitura crítica nas teses e dissertações brasileiras relacionadas à educação entre 1999 e 2018: uma metanálise - Marina Viana Bento (2020)
This research investigated the concept of critical reading adopted by authors of academic master's dissertations, professional master's dissertations and doctoral theses related to education and developed in postgraduate programs in Brazil between 1999 and 2018. The research is characterized as a meta-analysis guided by the theoretical-methodological principles of Content Analysis (BARDIN, 1977). Through the analysis of this material, we sought to: 1) characterize, categorize and correlate the concepts of critical reading adopted by the authors of these works; 2) list and analyze the bibliographic references on which the authors of these studies were based on the production of their research ; 3) map the temporal and geographical distribution of these studies. The corpus of this research was composed of 11 doctoral theses and 57 master's dissertations, totaling 68 works. The analysis of this material showed that the development of research on the topic of critical reading was intensified in graduate programs in Brazil between 2008 and 2018, mainly in the modalities of academic master and professional master. This intensification of interest on the subject was associated with the turbulent political and social moments that were experienced in Brazil at that time. Two definitions of critical reading were identified in the corpus: inferential critical reading, a view characterized by the ability to infer information; and engaged critical reading, portrayed as a social practice based on questioning and positioning the text. The analysis of the corpus also indicated that engaged critical reading is often associated with the notion of citizenship. Another aspect that stood out in the analysis process was the absence of a clear definition of critical reading in part of the research corpus. It was observed that the research was carried out mainly in the South and Southeast regions, but that there was a sharp increase in research on critical reading in the Northeast region. In addition, it was found that two institutions stood out quantitatively in the production of these studies: the Pontifícia Universidade Católica de São Paulo and the Universidade Federal do Rio Grande do Norte. The author most cited as a bibliographic reference among the examined theses and dissertations was Freire (1969, 1970, 1988, 1994, 1996, 2005). Finally, the carried out meta-analysis showed us a certain diversity of critical reading concepts adopted by the authors of these studies and revealed the existence of interest in this topic in several graduate institutions in Brazil. The analysis produced also identified gaps left by these works on the theoretical bases that support concepts of critical reading adopted by the authors on this topic.